A detailed analysis of treatment delay from the onset of symptoms in early rheumatoid arthritis patients. (January 2014) - De Cock, D; Meyfroidt, S; Joly, J; Van der Elst, K; Westhovens, R; Verschueren, P; ,
Abstract : Objectives: A treatment delay of more than 12 weeks can negatively affect treatment response in rheumatoid arthritis (RA). Our aim was to quantify the different stages of delay before RA treatment in different rheumatology centres and to explore influencing factors. Method: A total of 156 disease-modifying anti-rheumatic drug (DMARD)-naive early RA patients were included from eight practices: one academic hospital, five general hospitals, and two private practices. Eight different types of delay were defined from symptom onset until treatment initiation. Information on the duration of each stage of delay was collected from the patient, their general practitioner (GP), and patient files at the rheumatology practice. Patient/GP demographics and disease activity/severity parameters were recorded. Results: The median total delay from symptom onset until treatment initiation was 23 weeks whereas patient-, GP- and rheumatologist-related median delay was 10, 4, and 7 weeks, respectively. Only 21.6% of the patients had a total delay of less than 12 weeks. The total median delay in private rheumatology practices was less than in academic and general hospitals (p < 0.001). Furthermore, RA patients treated within 12 weeks of symptom onset showed a higher level of disease activity. The duration of rheumatologist-related delay was inversely correlated with disease activity parameters. Patients with morning stiffness were treated, on average, 3 weeks sooner than those without morning stiffness (p < 0.006). Conclusions: In only one out of five early RA patients was treatment initiated within 12 weeks of symptom onset, as recommended. Patient-related delay contributed most to overall delay. Disease activity and type of rheumatology centre are pivotal determinants of delay.